No longer a stranger: a cross-country longitudinal analysis of immigrant economic and social integration - Gameiro, Gonçalo Miguel De Almeida (2022)
Migrants’ integration has been a hot topic for most countries around the world. Are economic and social integration processes similar across countries? Using a novel collection and harmonization of data from the world's largest and longest-running panel surveys of five countries from 2001 to 2019, we show that an extra year in the destination increases earnings by 6%-12% and the probability of employment by 1.3%-2.5%. We find innovative evidence that one extra year since migration, increases the probability of contacting with neigh bors by 0.6%-2.3%, and the likelihood of belonging to community groups by 1.6%-3.7%.